Sensitivity study on the discretionary numerical model assumptions in the seismic assessment of existing buildings. Issue 98 (July 2017) - Pianigiani, M.; Mariani, V.
Abstract: In this work the main assumptions to be made in the seismic assessment of existing RC buildings have been assessed, in order to evaluate how much each of them can affect the obtained evaluation of the building safety, with reference to a case-study structure. Eurocode 8 provides all the information needed to perform the seismic assessment of existing buildings. Even if all the provided prescriptions are followed, in several assumptions a large subjectivity is left to the engineer in charge of the analysis. In this work the scatter related to such choices is evaluated with reference to a case-study building: a real RC Italian building currently used as a hospital. The contemplated assumptions concern the material characterization, the seismic input definition, the type of performed analysis and the set-up of the numerical model adopted to be representative of the building behaviour. The effects of each of these assumptions have been assessed in terms of scatter induced in the assumed response parameters, in order to evaluate the role of the discretionary choices in the seismic assessment. The results presented in this paper are representative of the analysed case-study building only, but aim at putting a spotlight to the effect that some too discretional prescriptions of the technical codes can have on the seismic assessment of existing structures. Highlights: Effect of discretionary modelling choices on the seismic assessment of RC buildings. Sensitivity study on a case-study building to predefined discretionary assumptions. Effect of some too discretional prescriptions of the codes can is relevant. Evaluation of safety can potentially be largely affected by selected assumptions.